Portrayal of Corruption in the Novel Devil on the Cross by Ngugi Wa Thiong’o. - Natumanya, Blessed (Kabale University, 2025)
The study was about the Portrayal of Corruption in the novel Devil on the Cross by Ngugi wa Thiong’o. The study was to be guided by the following Objectives: first, to analyze Ngugi Wa’Thiongo's portrayal of corruption in Devil on the Cross, second, to investigate the underlying causes and motivations driving the instances of corruption depicted in Devil on the Cross and third, to evaluate the impact of corruption on the lives of characters within the novel. This study employed a qualitative research design and a close reading that explored the elements of corruption in the novel Devil on the Cross by Ngugi Wa Thiongo. I used this approach to examine the text in contextual analysis and interpretation of Ngugi wa Thiong'o's idea of corruption in the novel. The research technique used was a close reading of the novel Devil on the Cross and analyzing the themes, symbols, and techniques of writing. Critical works relevant to the area of representation of corruption in post-colonial African countries were also considered. The data that was collected for the study was analyzed through close reading and textual analysis and I identified the forms of corruption in the novel Devil on the Cross by Ngugi Wa'Thiongo. In the discussion chapter, I discuss different forms of corruption which include; nepotism, bribery, fraud corruption, moral corruption, political corruption, and extortion as portrayed in Devil on the Cross. I also discuss the causes and motivations driving the instances of corruption in the novel as well as the impacts of corruption on the lives of characters in the novel.